Pronunciation and Conversation Challenges among Saudi EFL Students: Tantangan Pengucapan dan Percakapan di antara Siswa EFL Saudi - Naser, Issa Mohammad Muflih; Hamzah, Mohd Hilmi Bin (Universitas Muhammadiyah Sidoarjo, 2018)
This study aims to identify the difficulties of pronunciation and conversation faced by EFL learners who undertook a Preparatory Year Program (PYP) in Saudi Arabia, It highlights the main issues in pronunciation and conversations (e.g., textbooks, teaching methods, and students' attitude and motivation) and techniques to address these problems. The instruments used in the study were classroom observations and teachers' discussions. The results revealed that firstly, students did not have a sound knowledge of grammar. Secondly, students' outside environment was influenced by their mother tongue. Thirdly, the teaching methods did not suit their proficiency levels. Finally, they were demotivated and thought that they have an impossible mission to improve their English pronunciation and conversation.